PPA Preventive Fire System - Rizqi Fauzan Muhammad; Mirzai Baidawi (Eduvest - Journal of Universal Studies, 2024)
Fire incidents are something that every company must be aware of, because they can cause material and non-material losses. To deal with fires, a fire prevention and control system is needed. This system emphasizes preparation to prevent fires and can handle fires. However, the existence of a fire prevention and control system does not guarantee that a fire will not occur unless the fire prevention and control system is implemented well. Fire prevention program from PT PPA is a very important program to maintain the security, safety and successful operation of company facilities. Companies in the fuel storage area. The PPA preventive fire system is a digitalization program for detecting early indication of a series of fires. In principle, the PPA preventive fire system takes temperature readings in the fuel storage area which can then provide notifications or alerts to stakeholders in the fuel storage area using a certain algorithm so that they can provide messages via SMS (Short Message Service), WhatsApp Message and E-Mail. . Implementation of this system is an important step in mining work areas as the first preventive measure in the event of a fire.